Role of community pharmacists in the use of antipsychotics for behavioural and psychological symptoms of dementia (BPSD): a qualitative study. Issue 3 (16th March 2016) - Maidment, Ian D; Aston, Lydia; Hilton, Andrea; Iqbal, Naveed; Child, Anne; Shaw, Rachel
Abstract : Objective: This study aimed to use qualitative methodology to understand the current role of community pharmacists in limiting the use of antipsychotics prescribed inappropriately for behavioural and psychological symptoms of dementia. Design: A qualitative study employing focus groups was conducted. Data were analysed using thematic analysis. Setting: 3 different geographical locations in the England. Participants: Community pharmacists (n=22). Results: The focus groups identified an array of factors and constraints, which affect the ability of community pharmacists to contribute to initiatives to limit the use of antipsychotics. 3 key themes were revealed: (1) politics and the medical hierarchy, which created communication barriers; (2) how resources and remit impact the effectiveness of community pharmacy; and (3) understanding the nature of the treatment of dementia. Conclusions: Our findings suggest that an improvement in communication between community pharmacists and healthcare professionals, especially general practitioners (GPs) must occur in order for community pharmacists to assist in limiting the use of antipsychotics in people with dementia. Additionally, extra training in working with people with dementia is required. Thus, an intervention which involves appropriately trained pharmacists working in collaboration with GPs and other caregivers is required. Overall, within the current environment, community pharmacists question the extent to which they can contribute in helping to reduce the prescription of antipsychotics.